Ostwald Ripening of the InAsSbP/InAs(100) Quantum Dots in the Framework of the Modified LSW Theory - B.V. Ivanskii; R.D. Vengrenovich; V.I. Kryvetskyi; Yu.M. Kushnir (Журнал нано- та електронної фізики)
The analysis of quantum dots (QD) growth in InAsSbP/InAs (100) structure at the stage of Ostwald ripening (OR) is carried out in the frames of generalized LSW theory. It is found that after 30 minute growing of InAsSbP QD, their size distribution is well approximated by generalized Lifshitz–Slyozov–Wagner distribution. The growth of QD in the OR process is governed simultaneously by two mechanisms, namely, bulk diffusion and chemical reaction. At shorter time of QD growth, OR stage occurs partially (20 min) or does not occur at all (10 min).